CanVasc recommendations for the management of antineutrophil cytoplasm antibody (ANCA)-associated vasculitides – Executive summary. Issue 1 (December 2015) - McGeoch, Lucy; Twilt, Marinka; Famorca, Leilani; Bakowsky, Volodko; Barra, Lillian; Benseler, Susan; Cabral, David; Carette, Simon; Cox, Gerald; Dhindsa, Navjot; Dipchand, Christine; Fifi-Mah, Aurore; et al.
Abstract The Canadian Vasculitis research network (CanVasc) is composed of physicians from different medical specialties, including rheumatology and nephrology and researchers with expertise in vasculitis. One of its aims was to develop recommendations for the diagnosis and management of antineutrophil cytoplasm antibody (ANCA)-associated vasculitides in Canada. This executive summary features the 19 recommendations and 17 statements addressing general AAV diagnosis and management, developed by CanVasc group based on a synthesis of existing international guidelines, other published supporting evidence and expert consensus considering the Canadian healthcare context.